Redesign of the Packaging Design of Tempe-Sagu Chips Products Based on Customer Preferences Using Kansei Engineering and the Kano Model - Mukhlishotul Mabrurotin; Akmal Suryadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Neng Anis is a Small and Medium Enterprises located in Bojonegoro Regency which produces tempeh-sago chips which require improvements in product packaging so that they can compete for a wider market share with other tempeh-sago chips products. The aim of this research is to redesign the packaging design for tempeh-sago chips products based on customer preferences using Kansei Engineering and the Kano Model. This research used an interview method with the owner of the Neng Anis MSME and with 5 customers who had bought Neng Anis's tempe-sago chips. A 10 kansei word differential semantic questionnaire with 8 stimuli was distributed to 51 customers who had previously purchased Neng Anis tempe-sago chips products. The questionnaire results were processed using factor analysis, modified canoe diagram mapping and conjoint analysis. The packaging design for Neng Anis's sago tempeh chips that customers prefer is a packaging design that is Safe, Practical, Beautiful, Eye Catching, Unique, Informative, Elegant and Modern. The results of the packaging design use a box with a dark base color and use simple packaging decoration. Evaluation of the 3D design of Neng Anis sago tempeh chips packaging by 10 customers showed an average score of 86.5, indicating a positive response.